2013
DOI: 10.1103/physrevd.88.096009
|View full text |Cite
|
Sign up to set email alerts
|

Electroweak phase transition in the reduced minimal 3-3-1 model

Abstract: The electroweak phase transition is considered in framework of the reduced minimal 3-3-1 model (RM331). Structure of phase transition in this model is divided into two periods. The first period is the phase transition SU(3) ---> SU(2) at TeV scale and the second one is SU(2)--> U(1), which is the like-Standard Model electroweak phase transition. When mass of the neutral Higgs boson (h_1) is taken to be equal to the LHC value: m_{h_1}=125 GeV, then these phase transitions are the first order phase transitions, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…In a previous work [37], we have considered the EWPT in the reduced minimal 3-3-1 (RM331) model due to its simplicity, and found that our approach can be applied to the more complicated 3-3-1 models. In the present work, we follow the same approach for the economical 3-3-1 (E331) model [38][39][40][41][42][43][44], whose lepton sector is more complicated than that of the RM331 model.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work [37], we have considered the EWPT in the reduced minimal 3-3-1 (RM331) model due to its simplicity, and found that our approach can be applied to the more complicated 3-3-1 models. In the present work, we follow the same approach for the economical 3-3-1 (E331) model [38][39][40][41][42][43][44], whose lepton sector is more complicated than that of the RM331 model.…”
Section: Introductionmentioning
confidence: 99%
“…This phase transition involves exotic quarks, heavy bosons, without involvement of the SM particles, so υ ρ is omitted in this phase transition. The effective potential can be rewritten as follows (Phong et al, 2013):…”
Section: Phase Transition In Reduced Minimal 3-3-1 Modelmentioning
confidence: 99%
“…[2,4,5] as well as its various extended versions [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. For the SM, although the EWPT strength is larger than unity at the electroweak scale, the mass of the Higgs boson must be less than 125 GeV [2,4,5]; so the EWBG requires new physics beyond the SM at the weak scale [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many extensions such as the two-Higgs-doublet model, the reduced minimal 3-3-1 model, the economical 3-3-1 model, or the minimal supersymmetric standard model, have a strongly first-order EWPT and the new sources of CP violation, which are necessary to account for the BAU; triggers for the first-order EWPT in these models are heavy bosons or dark matter candidates [7][8][9][10][11][16][17][18]20]. However, most research of the EWPT are the Landau gauge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation